Pengaruh Agen Pengikat Silang dan Waktu Polimerisasi Poli Asam Tanat pada Efisiensi Dye Sensitized Solar Cell (DSSC) - Yusnita Pitri Mayenti; Hardeli Hardeli; Hary Sanjaya; Sri Benti Etika (Jurnal Periodic Jurusan Kimia UNP, 2021)
Abstract— Dye sensitized solar cell (DSSC) is a device that can convert light energy into electrical energy. Research on the DSSC continues to look for DSSCs with high efficiency values. The efficiency of DSSC is influenced by many things, one of which is the ability of the dye to absorb light energy. The dye used in this research is poly tannic acid obtained from the polymerization process of tannic acid. This polymerization is carried out to improve the ability of the dye to absorb sunlight. TiO2 / Cu paste was made using the sol gel method and coated on ITO glass using the doctor blade method. The formed layer is immersed in dye while the counter electrode is made with a candle flame. The DSSC was assembled to form a sandwich structure and electrolyte was dropped on the two electrodes. DSSC measured the voltage generated with a multimeter. The results of the UV-Vis analysis on the polymerized dye showed a bathochromic shift and an increase in the absorbance value. The results of FTIR analysis on polymerized dyes appeared ether groups in the range 1050–1250cm-1. The presence of this ether group indicates the formation of tannic acid poly. The highest DSSC efficiency found with the polymerized dye was 7.69% with polymerization time of 14 hours and the volume of crosslinking agent (TMPGDE) 115µL.Keywords: DSSC, Polymerization, Tannic Acid, Poly Tannic Acid, Efficiency